Aksesibilitas Dengan Motivasi Ibu Hamil Dalam Melakukan Kunjungan ANC K1 Murni: Accessibility with Pregnant Women's Motivation to Perform Pure ANC K1 Visit - Ekawati, Ni Wayan (Jurnal Abdi Keperawatan dan Kedokteran, 2022)
The high maternal mortality rate can be prevented through the Antenatal Care service which is able to detect and handle cases of high risk adequately, creating healthy conditions for the mother during pregnancy. Objective To find out the effect of Accessibility and Motivation on the Behavior of Pregnant Mothers in Conducting Pure ANC K1 Visits in the work area of Birobuli Health Center in Palu, Central Sulawesi. The design was cross sectional. Population was all pregnant women The sample size is 35 respondents using Accidental sampling technique. Independent variables were accessibility, The dependent variable was motivation. Data was collected using a questionnaire, then the data were analyzed using the Spearment rho test with a significance level of α ≤ 0.05. The results showed that most respondents had sufficient accessibility as many as 20 respondents (57.1%), sufficient motivation as many as 21 respondents (60%), ANC K1 visit behavior as many as 26 respondents (76.3%), statistical tests on variables accessibility there was a relationship of Accessibility to the Behavior of Pregnant Women in Visiting ANC K1 Pure,  There was the influence of Accessibility and Motivation of Pregnant Women in Conducting Pure ANC K1 Wilayah Kerja Puskesmas Birobuli Kota Palu Sulawesi Tengah. Good accessibility will increase the motivation of mothers to make ANC visits.